Integrating agricultural sustainability into policy planning: A geo-referenced framework based on Rough Set theory. Issue 54 (December 2015) - Demartini, Eugenio; Gaviglio, Anna; Bertoni, Danilo
Highlights: Integrating agricultural sustainability into policy planning presents difficulties. A georeferenced model for policy planning support is proposed. Rough Set theory is used for data reduction and information induction. Data pre-processing and model evaluation methodologies are discussed. The proposed framework helps in recognizing patterns within agricultural areas. Abstract: We propose a geo-referenced framework for agricultural sustainability assessment aimed at supporting policy planning. The framework is based on Rough Set theory and (i) integrates the three pillars of sustainability; (ii) proposes an easy measurement of agricultural systems' ability to resist over time (agricultural resilience); (iii) offers easy-to-read results; and (iv) reduces the gap between researchers' analytical skills and decision-makers' needs. In the paper, a part of the framework, we present essential and practical notion of Rough Set theory and a case study based on Lombardy Region (Italy). Finally, some values and lacks of the method are discussed.